'More willing to carry on in the face of adversity': how beginner teachers facing challenging circumstances experience positive psychology coaching. An interpretative phenomenological analysis. Issue 1 (2nd January 2021) - Lucey, Cornelia; van Nieuwerburgh, Christian
ABSTRACT: Positive psychology coaching (PPC) is defined as activating positive psychology (PP) in an applied and systematic way through coaching (Passmore, J., & Oades, P. (2014). Positive psychology coaching – A model for coaching practice. The Coaching Psychologist, 10 (2), 68–70). Currently studies looking at how PPC is experienced by coachees are limited. While there has been some early success cited in using a PPC approach in professional development in education with adults (Zwart, R. C., Korthagen, F. A. J., & Attema-Noordewier, S. (2014). A strength-based approach to teacher professional development. Professional Development in Education, 41 (3), 579–596. https://doi.org/10.1080/19415257.2014.919341) it is not yet known how teachers experience PPC. The purpose of this paper was to gain an understanding of how PPC is experienced by beginner teachers undergoing challenging circumstances. This initial explorative study adopted a qualitative approach using Interpretative Phenomenological Analysis (IPA) (Smith, J., Flowers, P., & Larkin, M. (2009). Interpretative phenomenological analysis: Theory, method and research . Sage). Four superordinate themes emerged: 'perfectly normal to feel this way'; making sense and 'joining the dots'; increased positive emotion; and, time to think 'in an easy-going environment'. Further studies of the application of PPC in educational settings are needed.